Impact of Covid-19 Pandemic on Economic Growth of the Tourism Sector in Indonesia - Mursalina Mursalina; Raja Masbar; Suriani Suriani (Research Collaboration Community (RCC), 2022)
Indonesia has made the tourism sector one of its current development priorities. However, the Covid-19 pandemic has harmed various economic sectors, and the tourism sector is the most affected in Indonesia. As a result of policies carried out by various countries including Indonesia, such as lockdown, social distancing, and its kind, economic activity has slowed, tourist arrivals have decreased drastically, and investment has decreased due to the uncertainty caused by the pandemic. This study aims to examine the effect of the Covid-19 pandemic on tourist arrivals and investment (domestic and foreign investment) and its impact on the economic growth of the tourism sector in Indonesia. This study uses the path analysis method by using mediating variables, namely tourist arrivals, and investment paths. Panel data regression is used to regress the path analysis equation, with data series 2018q1 – 2021q2 and cross-sections in 22 provinces in Indonesia that have tourist entrances.